Receiving and Capacitive Profile of Capacitors Arrangements on The Base of Butadiene-Styrene Rubber with Addition of CdCl2 or MoCl2 and Active Carbon - Borowski, Tomasz (Asian Journal of Chemistry, 2010)
In present studies, a method is developed for cheap capacitor materials with variable demand-dependent capacitance values in an easy way. Examination of capacitive properties was done at 20 °C. Mean capacitance range was between 0.8 and 8 F/g. The capacitive systems were examined on circuits with decade resistors and capacitors.